Impact of high-temperature processing steps on the long-term stability of charge carrier lifetime in n-type FZ-silicon - Mehler Melanie; Weinert Nicolas; Aßmann Nicole; Herguth Axel; Hahn Giso; Geml Fabian (EPJ Photovoltaics)
In this work, the long-term behavior of excess charge carrier lifetime in n-type FZ-Si wafers without presence of highly doped layers is investigated during illumination at elevated temperatures. Thereby, the influence of high-temperature processing steps such as short high temperature thermal treatment, often referred to as tabula rasa (TR), and phosphorus diffusion gettering is considered. Degradation of effective lifetime is observed as well as a very strong regeneration effect that significantly exceeds the initial effective lifetime value. The phosphorus gettering step appears to have no significant effect on the degradation and regeneration behavior. Samples subjected to a TR treatment show only bulk-related regeneration. Investigations in darkness showed that the bulk-related regeneration is carrier-induced and not necessarily light-induced. FT-IR measurements at 5 K showed that the samples with a TR step have a higher Oi concentration in the Si bulk and that the hydrogen-passivated vacancies (VH4) are dissolved. The regeneration behavior of the samples with a TR step could be correlated with a reduced vacancy concentration. Such a thermal processing step appears to offer a strong mitigation strategy.